A life-threatening condition - ruptured ectopic pregnancy with negative urine pregnancy test: a case report - Mohamad, Fadzilah; Yahya, Ahmad Shuib; Abdul Rashid, Aneesa; Devaraj, Navin Kumar; Abdul Manap, Abdul Hadi (Academy of Family Physicians of Malaysia, 2021)
Ectopic pregnancy is an extra-uterine pregnancy and is a potentially life-threatening condition that can lead to death from intra-peritoneal hemorrhage. This case reports a rare occurrence of ruptured tubal pregnancy in which the patient presented early with abdominal pain and a negative urine pregnancy test but subsequently presented again with evidence of intra-peritoneal hemorrhage. A negative urine pregnancy test is often used to rule out pregnancy, but it is not 100% sensitive. Complete assessment is critical in this important diagnosis in order to plan for the appropriate emergency management.